Granulomatous peritonitis caused by glove starch. Issue 695 (September 1983) - Michowitz, M.; Stavorovsky, M.; Ilie, B.
Abstract : Corn starch particles are used as a surgical glove lubricant. At present there is no better alternative for this lubricant. Implantation of corn starch particles into the peritoneal cavity can induce foreign body reactions, starch peritonitis and starch granulomata, and may cause adhesions and intestinal obstruction. Starch peritonitis should be treated conservatively.